EVALUASI PRAKTIKALITAS LKPD BERBASIS GUIDED INQUIRY PADA MATERI IKATAN KIMIA UNTUK SISWA KELAS X SMA - Setiani, Novenia (rc-institut, 2019)
This research aims to produce learning materials of worksheet based on guided inquiry learning  for chemical bonding topic which practicality. The designed worksheet graded by panellist from chemistry teachers and 26 students in high school. To collect data, practicality questionnaire were used as the instruments. The data analysis technique used in this research were percentage of practicality. The data in this research are primary data consisting of practicality. The result of practicality by teachers was very practice with value 94% and practicality by students was practice with value 75%.